Implementation of CPM and PERT Method in Canteen Development Project CV Super Makmur - PS, Pelik Pernandes; Puri, Pustika Ayuning; Nurhasanah, Siti (Westscience Press, 2024)
Project management is the science and art concerned with planning, organizing, implementing, and controlling projects to achieve predefined goals by utilizing available resources optimally. The CPM (Critical Path Method) method is a deterministic approach that identifies the longest path of activities in a project, while the PERT (Program Evaluation and Review Technique) method is used to plan, estimate and control completion time by considering the uncertainty in each project activity. The goal to be achieved from this research is that the application of the method and implementation of the CPM and PERT methods can optimize project completion by knowing critical activities, operations, estimated time, costs and project resources, as well as reducing the risk of delays and additional project costs. This research adopts a quantitative approach and applies descriptive analysis using the CPM and PERT methods. Based on the analysis results, it is known that there are two critical paths, namely A-C-E-I and B-D-G-K, so accelerating the project time without delaying or waiting for completion in 11 weeks, with a value of Z = 2.27 in the normal distribution table shows the number 0.9984, meaning the probability that the project can be completed during 11 weeks is 99%. because there is an additional fee of IDR 2,588,940 which is an additional acceleration fee. So, the cost of completing a 12-week project is IDR 1,171,739,257 while for 11 weeks it is IDR 1,174,328,197.